WARNA TERHADAP KENYAMANAN RUANG AVISHA WELLNESS & SPA JIMBARAN, BALI - Sampe Tandung, Astiany (Jurnal Teknik Sipil, Arsitek, Perencanaan Wilayah (J-TSIAP), 2024)
The development of life every year, every day always experiences changes both in terms of technology, needs and desires. From the point of view of needs, many young people, especially women, are now trending about body beauty to avoid wrinkles, dry skin and stay young. To fulfill their desires, alternatives are needed for their needs, one of the alternatives to this problem is to undergo therapy at a spa. It is necessary to pay attention to a comfortable and safe place to carry out therapy. One of the comforts of the therapy place is the color combination of the place. With the right combination of colors in the room, visitors will feel comfortable and can pamper their eyes so they can achieve good relaxation.